Tindak Pidana Penyadapan Dengan Modus Sniffing - Junior Teng Lewier; Deassy Jacomina Anthoneta Hehanussa; Iqbal Taufik (PATTIMURA Law Study Review, 2023)
Sniffing is the illegal interception and capture of data while traveling over a network using certain tools. The research method used is normative juridical using a regulatory-legislative approach, a conceptual approach and a case approach. The legal materials used are primary, secondary and tertiary legal materials. The analysis of legal materials used is qualitative analysis. The results of the research show that: there are several obstacles in overcoming criminal acts of fraud using the sniffing mode, namely Article 28 paragraph (1) of the ITE Law can only be used in criminal acts of online fraud which are characterized by online buying and selling activities only, whereas in Article 378 of the Criminal Code can only be used to ensnare perpetrators of conventional fraud crimes. Apart from that, overcoming criminal acts of fraud using the sniffing mode can be carried out with a penal policy of forming new laws that regulate sniffing, and non-penal measures which can be carried out by improving the economy and education.